Super-Adiabatic Combustion in Al2o3 and Sic Coated Porous Media for Thermoelectric Power Conversion - Bubnovich, V (Elsevier Ltd, 2013)
The combustion of ultra-lean fuel/air mixtures provides an efficient way to convert the chemical energy of hydrocarbons and low-calorific fuels into useful power. Matrix-stabilized porous medium combustion is an advanced technique in which a solid porous medium within the combustion chamber conducts heat from the hot gaseous products in the upstream direction to preheat incoming reactants. This heat recirculation extends the standard flammability limits, allowing the burning of ultra-lean and low-calorific fuel mixtures and resulting a combustion temperature higher than the thermodynamic equilibrium temperature of the mixture (i.e., super-adiabatic combustion). The heat generated by this combustion process can be converted into electricity with thermoelectric generators, which is the goal of this study.The design of a porous media burner coupled with a thermoelectric generator and its testing are presented. The combustion zone media was a highly-porous alumina matrix interposed between upstream and downstream honeycomb structures with pore sizes smaller than the flame quenching distance, preventing the flame from propagating outside of the central section. Experimental results include temperature distributions inside the combustion chamber and across a thermoelectric generator; along with associated current, voltage and power output values. Measurements were obtained for a catalytically inert Al2O3 medium and a SiC coated medium, which was tested for the ability to catalyze the super-adiabatic combustion. The combustion efficiency was obtained for stoichiometric and ultra-lean (near the lean flammability limit) mixtures of CH4 and air. © 2013 Elsevier Ltd.